Physiological effects of constant versus variable power during endurance cycling - Liedl, M. A.; Swain, D. P.; Branch, J. D. (Medicine & Science in Sports & Exercise, 1999)
The purpose of this study was to determine whether variable power (VP) cycling produced greater physiological stress than constant power (CP) cycling of the same mean intensity. Conclusion: During a strenuous 1-h effort (78% of VO2max), subjects experienced no additional physiological stress by varying power ± 5% compared with that during a constant power effort.